Health-Seeking Behavior of Urban Poor Communities - Olympia Malanyaon (Philippine Institute for Development Studies (PIDS), 1995)
Utilizing the Participatory Action Research (PAR) approach, this paper determines the socioeconomic conditions in relation to health care of the urban poor communities in Pasay and Novaliches. This investigates the communities' demographic characteristics, their perception towards health care and their willingness to participate in risk-sharing associated with health maintenance.
Keywords: 330; urban management; health sector; health care; health insurance; urban poor; risk-sharing